An eco-feminist reading of Mahasweta Devi - Sharma, Dr. Dinesh (Innovative Research Thoughts, 2018)
Some people's dissent is a way of life. When Mahasweta Devi isn't fighting for her beliefs as a political activist or academic or journalist or creative writer, she's outspoken. In India, she is widely regarded as one of the country's leading literary figures. As a prolific novelist, playwright, short storey collection, and children's book author, she has penned over a hundred volumes. In addition to Bengali, she has also translated her writings into English and other languages. She was inspired to become a writer and an activist because of the harsh realities and systemic injustice she witnessed. Bengali People's Theatre movement of Bengal, after Naxalite uprising of 1950s and her first-hand contact with Bihar, West Bengal and Madhya Pradesh and Chhattisgarh tribals affected her life and profession.